2002
DOI: 10.1177/002215540205000508
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Detection of Neuronal Nitric Oxide Synthase (nNOS)-IR in Embryonic Rat Stomach Between Days 13 and 21 of Gestation

Abstract: In this study, the localization and appearance of neuronal nitric oxide synthase-immunoreactive (nNOS-IR) nerve cells and their relationships with the developing gastric layers were studied by immunocytochemistry techniques and light microscopy in embryonic rat stomach. The stomachs of Wistar rat embryos aged 13-21 days were used. The first nerve cells containing nNOS-IR were seen on embryonic Day 14. The occurrence of mesenchymal cell condensation near nNOS-IR neuroblasts on embryonic Day 15 may reflect an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Despite the presence of enteric nitrergic neurons at this early stage, an NO‐mediated inhibitory tonus has been reported to be present only just before or at the onset of exogenous feeding (Holmberg et al, 2006). This is similar to what has been suggested for other vertebrate species (Timmermans et al, 1994; Van Ginneken et al, 1998, 2001; Bagyanszki et al, 2000; Belai and Burnstock, 2000; Bayram et al, 2002; Pederzoli et al, 2007). Furthermore, an additional role for nNOS has been proposed in the development and differentiation of the embryonic zebrafish gut (Holmqvist et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the presence of enteric nitrergic neurons at this early stage, an NO‐mediated inhibitory tonus has been reported to be present only just before or at the onset of exogenous feeding (Holmberg et al, 2006). This is similar to what has been suggested for other vertebrate species (Timmermans et al, 1994; Van Ginneken et al, 1998, 2001; Bagyanszki et al, 2000; Belai and Burnstock, 2000; Bayram et al, 2002; Pederzoli et al, 2007). Furthermore, an additional role for nNOS has been proposed in the development and differentiation of the embryonic zebrafish gut (Holmqvist et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…One of the possible reasons for the increased expression of synaptophysin‐immunoreactivity may be the markedly increased intramuscular innervation. In fact, in our previous study, we reported that the amount of the smooth muscle increased in parallel the innervations of the muscle layer (Bayram et al., 2002).…”
Section: Discussionmentioning
confidence: 83%